Unicompartmental Knee Arthroplasty In Medial Osteoarthritis Knee With Anterior Cruciate Deficiency: A Case Report - Fendy, Fendy (The Hip and Knee Journal, 2024)
Advantages of Unicompartmental Knee Arthroplasty (UKA) include the preservation of more tissue, maintenance of knee kinematics, and a faster recovery period. However historically absence of an ACL could affect knee stability and lead to various degenerative changes, such as intra-articular damage and knee instability. Case presentation a 60-year-old female patient presented with severe left medial knee pain and functional limitations and persisted with conservative treatment. Clinical examinations revealed tenderness over the medial joint line, a positive varus stress test, and a Lachman test. Radiographic imaging confirmed severe medial compartment osteoarthritis with ACL deficiency without significant damage to other knee structures. Patient was diagnosed with medial compartment osteoarthritis in an ACL-deficient knee. UKA using Oxford medial unicompartment implant was performed cement inserted into the medial compartment. The patient followed a routine rehabilitation program. At the 2 days after operation patient can full extension of the knee and flexion of the knee about 120 degree with minimal pain. Radiographic evaluation showed adequate implant positioning. The discussion several studies have shown that with meticulous patient selection and accurate surgical technique, UKA can yield favorable outcomes even in cases of ACL deficiency. Preserving the ACL is critical to the success of UKA but achieving good results in ACL-deficient patients if the joint proves stable and well-balanced intraoperatively is possible. The conclusion isUKA might be a viable option for patients with medial compartment osteoarthritis with ACL deficiency.